Endophytic PGPB Improves Plant Growth and Quality, and Modulates the Bacterial Community of an Intercropping System - Pardo-Díaz, Sergio; Romero-Perdomo, Felipe; Mendoza-Labrador, Jonathan; Delgadillo-Duran, Diego; Castro-Rincon, Edwin; Silva, Antonio M. M.; Rojas-Tapias, Daniel F.; Cardoso, Elke J. B. N.; Estrada-Bonilla, German A. (Frontiers in Sustainable Food Systems, 2021)
The intercropping of ryegrass and red clover constitutes a sustainable alternative to mitigate the adverse effects of intensive livestock production on grassland degradation by increasing forage yield and quality. The implementation of biofertilization technologies has been widely used to improve soil nutritional properties, and therefore has the potential to ensure the success of this multicrop system. To determine the impact of bioaugmentation on forage growth and quality, as well as the associate changes in the rhizosphere bacterial community, we evaluated the inoculation with two plant growth-promoting bacteria (PGPB) under reduced nitrogen usage. Overall, Herbaspirillum sp. AP21 had a larger effect than Azospirillum brasilense D7 on plant growth. Inoculation with Herbaspirillum sp. AP21 together with 50% of the required nitrogen rate increased shoot dry weight, crude protein, and shoot nitrogen content, and decreased the amount of neutral detergent fiber. PGPB inoculation changed the rhizosphere bacterial community structure, which associated with forage growth and quality. We conclude that PGPB inoculation has the potential to improve the growth of the ryegrass-red clover system, decreasing the requirements for nitrogen fertilization.